MUSEUMIFICATION OF THE REGION OR WHAT HISTORIES LOCAL COMMUNITIES NEED - Dokuchaev, D.S. (Perm Federal Research Centre Journal, 2015)
In the essay, the museum is regarded as a social and political institution, involved in the process of legitimation of regional identity. From the standpoint of the system and the semiotic approach the author discusses the process of museumification and its significance for the creation of the collective history of the local community.